Observation of Polypropylene (PP) Melt Flow on Microchannel Using Polymethyl Methacrylate (PMMA) Mold - Azuddin, M.; Zahari, T.; Choudhury, I.A. (Marcel Dekker (now owned by Taylor & Francis), 2011)
The flow of melted plastic in microparts is an interesting area to discover. Many studies have being conducted to understand the phenomena of polymer flow in microplastic parts. One type of study is the visualization of melted polymer flow. This work focuses on the observation of the micro-flow of melted Polypropylene (PP) using transparent polymethyl methacrylate (PMMA) mold. A PMMA mold with 0.5, 0.8, and 1.0 mm diameter channels were fabricated and injected with melted PP using a custom made vertical plastic injection molding machine. The flow of the melted PP can be clearly seen through the PMMA transparent mold. The result of the experimental are compared with a result from finite element analysis (FEA) software, MoldFlow Part Advisor. The result shows a good agreement for 1.0 and 0.8 mm channels, but not for the 0.5 mm. It can be concluded that, the analysis software is not capable of predicting the flow for 0.5 mm channel and less.